INCREASING THE CLASSICAL ACTIVITY OF FUTURE TEACHERS AS A PEDAGOGICAL AND PSYCHOLOGICAL PROBLEM (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article describes the current requirements for the professional training of future teachers, the importance of increasing cognitive activity, the hierarchical pyramid of teaching methods, the stages of acquisition of knowledge and the future of the teacher.